Primer of biostatistics statistical software program version 5.0 - Glantz, Stanton A. (New York : McGraw-Hill, 2002)
This menu-driven program performs meaningful analysis of your data quickly and easily. The CD-ROM provides online advice on which tests to run and printing results is as easy as point and click.
Keywords: Biometry